A soft-chemistry assisted strong metal–support interaction on a designed plasmonic core–shell photocatalyst for enhanced photocatalytic hydrogen production. Issue 13 (26th February 2020) - Gesesse, Getaneh Diress; Wang, Cong; Chang, Bor Kae; Tai, Shih-Hsuan; Beaunier, Patricia; Wojcieszak, Robert; Remita, Hynd; Colbeau-Justin, Christophe; Ghazzal, Mohamed Nawfal
Abstract : Engineering photocatalysts based on gold nanoparticles has emerged as new strategy to improve the solar energy conversion. Abstract : Engineering photocatalysts based on gold nanoparticles (AuNPs) has attracted great attention for the solar energy conversion due to their multiple and unique properties. However, boosting the photocatalytic performance of plasmonic materials for H2 generation has some limitations. In this study, we propose a soft-chemistry method for the preparation of a strong metal–support interaction (SMSI) to enhance the photocatalytic production of H2 . The TiO2 thin overlayer covering finely dispersed AuNPs (forming an SMSI) boosts the photocatalytic generation of hydrogen, compared to AuNPs deposited at the surface of TiO2 (labelled as a classical system). The pathway of the charge carriers' dynamics regarding the system configuration is found to be different. The photogenerated electrons are collected by AuNPs in a classical system and act as an active site, while, unconventionally, they are injected back in the titania surface for an SMSI photocatalyst making the system highly efficient. Additionally, the adsorption energy of methanol, theoretically estimated using the density functional theory (DFT) methodology, is lower for the soft-chemistry SMSI photocatalyst accelerating the kinetics of photocatalytic hydrogen production. The SMSI obtained by soft-chemistry is an original concept for highly efficient photocatalytic materials, where the photon-to-energy conversion remains a major challenge.